Development of Nomor Acak Learning Models to Increase Studentâs Learning Effectivity at PGSD FKIP University of Riau - Syahrilfuddin, Syahrilfuddin; Zufriady, Zufriady (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The developing of nomor acak learning model aims to improve the effectiveness of studentsâ learning in some subjects. This learning model emphasises on studentsâ readiness on learning process. This research implemented Research and Development method with four stages which are literature review, designing model, implementation and evaluation, and editing and publication. In designing model random number, it was found five learning syntaxes that consists of preparation, implementation of nomor acak model in learning process, evaluation, conclusion, and giving motivation. After applying this method four times, questionnaire was given to 83 students for evaluation, and the result showed that this method can improve learning effectiveness at level of 79,83%. It can be concluded that random number learning model can improve learning effectiveness.